PENGARUH PROFESIONAL JUDGEMENT, PENGALAMAN, KEAHLIAN, PENGETAHUAN AKUNTANSI DAN AUDIT SERTA SKEPTISME AUDITOR TERHADAP KETEPATAN PEMBERIAN OPINI AUDITOR - Pardede, Hendriko; Rasuli, Muhammad; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was examining the influence of Profesional judgement, Experience, expertise, knowledge of accounting and auditing, auditor’s professionalism scepticism and the accuracy of audit opinion. Respondents in this study were auditors who worked for the Public Accounting Firm in Palembang, Medan, Pekanbaru. The number of auditor involved in this study were 67 auditors from 14 Public Accounting Firm in Jakarta. The method of determining the sample was using purposive sampling method, while the data processing methods used by researcher was the multiple regression analysis. The result shows that Profesional Judgement, Experience and expertise did not have significantly influence to the accuracy of audit opinion, whereas knowledge of accounting and auditing, and auditor’s professionalism scepticism had significantly and positively influence to the accuracy of audit opinion.Keywords: Profesional judgement , Experience, expertise, knowledge of accounting and auditing, auditor’s professioalism scepticism, the accuracy of audit opinion